Enhancing Data Utilization in Human Development Programmes: A Structured Programme Analytical Framework for Improved Decision-Making - , Asseneth Jerotich Cheboi; , Boniface Francis Kalanda (Archives of Current Research International, 2025)
Programme data analysis, often the weakest link in the management of human development programmes, undermines the quality of programmes and delivery of results. Organizations implementing human development programmes have vast amounts of programme monitoring data collected through various data collection methods such as field monitoring visits, surveys, and interviews. Often, these data are not optimally used because of a lack of an established and institutionalized Programme Analytical Framework (PAF). In this study, the need for a structured approach for an organization implementing human development programmes to analyse programme data using a Programme Analytical Framework (PAF) has been highlighted. In the Theory of Change (ToC) which sought to articulate the key issues and pathways of change to improve programme analyses, we identified three key issues – organizational culture change, skills for analysis and an analytical framework – as the critical enablers for improved analysis in an organization. Furthermore, the paper outlines the various areas of focus for analysis to be considered when developing a Programme Analytical Framework (PAF) and the emphasis on the dissemination of analytical products with actionable insights for use in decision-making. Overall, this proposed Programme Analytical Framework (PAF) seeks to improve the analysis and use of programme data which ultimately improves the quality and delivery of results for human development programmes.